2017
DOI: 10.1167/17.14.10
|View full text |Cite
|
Sign up to set email alerts
|

The effects of delay duration on visual working memory for orientation

Abstract: We used a delayed-estimation paradigm to characterize the joint effects of set size (one, two, four, or six) and delay duration (1, 2, 3, or 6 s) on visual working memory for orientation. We conducted two experiments: one with delay durations blocked, another with delay durations interleaved. As dependent variables, we examined four model-free metrics of dispersion as well as precision estimates in four simple models. We tested for effects of delay time using analyses of variance, linear regressions, and neste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 62 publications
(113 reference statements)
5
23
2
Order By: Relevance
“…Model fits indicated that random guessing increased with time for human subjects (Fig. S10), consistent with previous literature (3)(4)(5). Guessing decreased with delay, however, for the two monkeys.…”
Section: Dynamic Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…Model fits indicated that random guessing increased with time for human subjects (Fig. S10), consistent with previous literature (3)(4)(5). Guessing decreased with delay, however, for the two monkeys.…”
Section: Dynamic Modelsupporting
confidence: 89%
“…We quantified error as the angular deviation between the target color and the subject's report. As expected (3)(4)(5)(6)(7)(8)(9)(10), the average absolute error increased as a function of delay and working memory load ( Fig. 1b; humans (H): load, F (1, 89) = 147.23, p < 0.001; delay, F (1, 89) = 85.44, p < 0.001; load x delay, F (1, 89) = 13.92, p < 0.001; monkey W (W): load, p < 0.001; delay, p = 0.006; load x delay, p = 0.495; monkey E (E): load, p < 0.001; delay, p = 0.009; load x delay, p = 0.303).…”
Section: Main Textsupporting
confidence: 87%
See 1 more Smart Citation
“…5. Forego modeling altogether and compare across conditions only model-free summary statistics, such as mean absolute error, circular variance, or circular standard deviation (Van den Berg et al, 2017;Shin et al, 2017;Rademaker et al, 2012;Pertzov et al, 2017;Emrich et al, 2017). This is my best recommendation if the purpose of a study is not model comparison but a characterization of some independent variable on working memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such a convincing win might be rare, though: usually, the VP model fits as well or somewhat better (Van denBerg et al, 2014Berg et al, , 2017.3. Ensure that any inferences drawn from a comparison across conditions are independent of the fitted model(Shin et al, 2017). The disadvantages of this approach are that it is more work and that a decision must be made on how to aggregate results that are not completely consistent across models.…”
mentioning
confidence: 99%